2018
DOI: 10.1111/sdi.12719
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in conventional hemodialysis: Finding the optimal treatment balance

Abstract: Renal anemia is a serious and common complication in hemodialysis (HD) patients.The introduction of erythropoiesis-stimulating agents (ESAs) has dramatically improved hemoglobin levels and outcomes. Several interventional studies reported that excessive correction of anemia and the massive use of ESA can trigger cardiovascular disease (CVD), and consequently may worsen the prognosis of patients undergoing HD. Therefore, it has been widely recognized that large doses of ESA should be used with caution. An effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…ERFE is synthesized in erythroblasts in response to increased erythropoiesis and it suppresses transcription of hepcidin in hepatocytes and thus increases iron availability in conditions associated with greater iron demand [16]. In murine models, ERFE deficiency is associated with mild hypochromic anemia and delayed hepcidin suppression following hemorrhage or EPO injection, while in certain conditions with ineffective erythropoiesis, such as β-thalassemia, ERFE concentrations were significantly increased [17] (Fig. 2).…”
Section: Role Of Hepcidinmentioning
confidence: 96%
See 2 more Smart Citations
“…ERFE is synthesized in erythroblasts in response to increased erythropoiesis and it suppresses transcription of hepcidin in hepatocytes and thus increases iron availability in conditions associated with greater iron demand [16]. In murine models, ERFE deficiency is associated with mild hypochromic anemia and delayed hepcidin suppression following hemorrhage or EPO injection, while in certain conditions with ineffective erythropoiesis, such as β-thalassemia, ERFE concentrations were significantly increased [17] (Fig. 2).…”
Section: Role Of Hepcidinmentioning
confidence: 96%
“…A new group of oral agents known as HIF prolyl hydroxylase-inhibitors has been developed to improve CKD-associated anemia. The beneficial effect of HIF stabilizers on hemoglobin levels has been observed regardless of the patient's iron stores and inflammatory status [17]. However, the long-term safety of these novel agents, especially regarding potential risk of tumorigenesis and worsening of proliferative diabetic retinopathy, has yet to be established [17,96].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Around the time that EPO received FDA approval in 1989 for treatment of anemia in chronic renal disease, death associated with EPO doping was suspected in eighteen young professional cyclists who died from unknown causes (Noakes, 2004). While patients with renal failure clearly benefit from EPO treatment to correct anemia (Eschbach et al, 1987;Us Renal Data System, 2007;Hasegawa et al, 2018) several clinical trials of EPO treatment to normalize hemoglobin values in kidney disease showed increase cardiovascular morbidity and mortality associated with high dose EPO treatment (Drueke et al, 2006;Singh et al, 2006). With increased concerns about safety of high dose EPO, the FDA issued a "Black Box" warning in 2007 indicating reduced EPO dose to achieve lower target hemoglobin levels.…”
Section: Elevated Epo In Human and Decreasing Obesity Prevalence At Imentioning
confidence: 99%
“…Hamano describes the various measures for the management of MBD in hemodialysis patients, and summarizes current evidence evaluating their effects on clinical outcomes . Hasegawa et al then elaborate on data examining the target hemoglobin levels with the use of currently available treatment options for anemia management in conventional hemodialysis patients, and debate their optimal treatment balance …”
mentioning
confidence: 99%